Jose Monserrat Maceda breaking music's frontiers - National Commission for Culture and the Arts; Santos, Ramon; Red, Jon.; De la Cruz, Libertine Santos ([Pasay City] Cultural Promotions Division, Cultural Resources Dept., Cultural Center of the Philippines, 2002)
Documents Jose Monserrat Maceda's life-long dedication to the understanding and popularization of Filipino traditional music. His compositions, like Ugma-ugma (1963), Pagsamba (1968), and Udlot-udlot, are monuments to his unflagging commitment to Philippine music. Maceda's music, researches and fieldwork enlighten the scholar, both Filipino and foreign, about the nature of Philippine traditional and ethnic music.
"Maceda : national artist for music"--Cover.
VCD.
Narrated by Jaime Fabregas.